Penerapan Metode CPM (Critical Path Method) Pada Proyek Peningkatan Sarana Dan Prasarana TPS Limbah dan Fasilitasnya Di PT. Putra Kuala Tanjung - Syahputra, Rahmad; Pasaribu, Muhammad Fazri; Syarif , Abdul Azis (CV. IRA PUBLISHING, 2024)
In construction projects, inaccuracies in planning procedures often lead to failures or delays. Given the importance of timely project completion in the competitive construction service industry, the Critical Path Method (CPM) is recommended for scheduling. This method allows for highly detailed time planning by breaking down the work into small items, enabling accurate duration calculations for each activity. This study focuses on rescheduling the construction of the Preprocessing Building (steel structure) at PT. Putra Kuala Tanjung's project. By breaking down the work and performing forward and backward calculations, the author successfully determined the duration of each activity and identified critical tasks. As a result, the project duration was reduced from 252 working days to 156 days, demonstrating a time savings of 96 days.